Specific anesthesia‐induced lung volume changes from induction to emergence: a pilot study. Issue 3 (3rd November 2017) - Kostic, P.; LoMauro, A.; Larsson, A.; Hedenstierna, G.; Frykholm, P.; Aliverti, A.
Abstract : Background: Studies aimed at maintaining intraoperative lung volume to reduce post‐operative pulmonary complications have been inconclusive because they mixed up the effect of general anesthesia and the surgical procedure. Our aims were to study: (1) lung volume during the entire course of anesthesia without the confounding effects of surgical procedures; (2) the combination of three interventions to maintain lung volume; and (3) the emergence phase with focus on the restored activation of the respiratory muscles. Methods: Eighteen ASA I–II patients undergoing ENT surgery under general anesthesia without muscle relaxants were randomized to an intervention group, receiving lung recruitment maneuver (LRM) after induction, 7 cmH2 O positive end‐expiratory pressure (PEEP) during anesthesia and continuous positive airway pressure (CPAP) during emergence with 0.4 inspired oxygen fraction (FiO2 ) or a control group, ventilated without LRM, with 0 cmH2 O PEEP, and 1.0 FiO2 during emergence without CPAP application. End‐expiratory lung volume (EELV) was continuously estimated by opto‐electronic plethysmography. Inspiratory and expiratory ribcage muscles electromyography was measured in a subset of seven patients. Results: End‐expiratory lung volume decreased after induction in both groups. It remained low in the control group and further decreased at emergence, because of active expiratory muscle contraction. In the intervention group, EELV increased after LRM and remained high after extubation. Conclusion: A combined intervention consisting of LRM, PEEP and CPAP during emergence may effectively maintain EELV during anesthesia and even after extubation. An unexpected finding was that the activation of the expiratory muscles may contribute to EELV reduction during the emergence phase.